2003
DOI: 10.1016/s0031-9422(03)00426-6
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside

Abstract: Stevioside is a natural sweetener extracted from leaves of Stevia rebaudiana (Bertoni) Bertoni. The literature about Stevia, the occurrence of its sweeteners, their biosynthetic pathway and toxicological aspects are discussed. Injection experiments or perfusion experiments of organs are considered as not relevant for the use of Stevia or stevioside as food, and therefore these studies are not included in this review. The metabolism of stevioside is discussed in relation with the possible formation of steviol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
0
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(298 citation statements)
references
References 46 publications
5
264
0
29
Order By: Relevance
“…In S. rebaudiana , UGTs trigger the downstream steps in the synthesis of steviol glycosides 1. The transcription of UGT85C2 and UGT76G1 genes showed a significant reduction in polyethylene glycol treatment which is supported by other reports 16, 27.…”
Section: Discussionsupporting
confidence: 76%
“…In S. rebaudiana , UGTs trigger the downstream steps in the synthesis of steviol glycosides 1. The transcription of UGT85C2 and UGT76G1 genes showed a significant reduction in polyethylene glycol treatment which is supported by other reports 16, 27.…”
Section: Discussionsupporting
confidence: 76%
“…This feature is an advantage for steviolbioside 2 sweetener's utility in foods and beverages. Steviosides are commonly used as natural sweeteners in beverages and foods (Geuns 2003). Their main characteristics include their thermal stability up to 238°C, resistance to acid hydrolysis, they are not fermentable, and most importantly nontoxic.…”
Section: Physical Characteristics Of Steviolbioside Sweetenermentioning
confidence: 99%
“…Stevioside 1 is the prevalent sweetener, accounting for 3-12% (w/w) of dried leaves and 90% in total glycosides with a sweetening potential 300 times that of sucrose and is known to be noncaloric (Moussa et al 2003;Chatsudthipong and Muanprasat 2009). Minor components are present in this plant, including rebaudiosides (B, C, F), steviolbioside 2 and dulcoside A (1-2% in total) (Geuns 2003). Some evidence confirms that steviolbioside and rebaudioside B are not genuine constituents of S. rebaudiana but are rather formed by partial hydrolysis during the extraction process (Kim and Dubois 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The economic importance of stevioside (78), derived from its great world-wide consumption, has motivated diverse work aiming to characterize and establish the safe levels of this kaurane glycoside and its metabolites in the human organism [106,107]. Although some work has failed to demonstrate carcinogenic, teratogenic, mutagenic or toxic actions of stevioside (78), after oral administration to rats [108][109][110][111], at doses up to 1.2 % of the diet, and considering, therefore, a maximum ingestion recommendable of 7.94 mg·kg -1 ·d -1 for the human organism [112], others have demonstrated that steviol (24), an aglycone obtained from complete hydrolysis of stevioside, showed a high toxicity in pregnant females and embryos of hamsters, at doses of 0.75 and 1.00 mg·kg -1 ·d -1 , administered from 6 th to 10 th day of gestation [112][113][114].…”
Section: R' = R" = Hmentioning
confidence: 99%